AIDS e religiosidade: influências intersubjetivas aos acometidos pela epidemia - Silva, Paulo Emanuel (2009)
Nowadays, despite all the information related to several types of diseases, some of them are still cause for anxiety, fears and prejudices. In ancient leprosy and the plague and from the nineteenth century, cancer, syphilis and tuberculosis, permeated the mentality and marked their bearers, as the meanings of illness were different than their symptoms, something similar is happening in the contemporary world as with respect to Acquired Immunodeficiency Syndrome (AIDS). For many, the positivity for HIV understood here as the person with HIV is still synonymous with death, in this sense, the person is stimulated to profound reflections on life itself, if it was satisfactory trajectory of their life, if there were any emotional development, to create strong emotional bonds and permanent or if it could help other human beings. Thus the beliefs, opinions, personal values and group should be valued and considered in the dialogue both in format and content of the approaches in the field of health promotion. To assess the quality of life of HIV / AIDS in the city of João Pessoa / PB; investigate the influence of religiosity in the face of aids; check the influence of the "race" or color along religious factor in the way of coping positivity for HIV. This is a descriptive exploratory study with quantitative and qualitative approach, performed in a reference hospital in the city of João Pessoa. We interviewed 76 people, this sample was found that 50% of the study participants were male and 50% female, with age in both sexes ranging from 20 to over 60 years, was also found that most of the interviewees belong to black with little schooling. When you make a cross between the level of education and purchasing power can be seen that this, combined with low education increases the evidence about the pauperization of the epidemic. As for the religious profile was observed a high incidence among Catholics and evangelicals. The approach to the senses perceive in the study show that the diagnosis of AIDS appears to involve meanings in people, surprise and mental pain due to waiting an outcome uncertain, so much that they have no fear of the future in not to keep large prospects. This reinforces the need for interdisciplinary care of all HIV positive and not only with the patient of aids with the goal of building with them, other senses to life and even opportunities for them to feel involved in the process of overcoming the disease. From the religious approach found that the "face of aids" can no longer be a "face" of death, but a "face" of life, because people try to learn to live with the disease, making their day-to-day in a "battle" to find a constant sense of life, so to redeem the respect and dignity, and thus decimating the stigma of the epidemic caused in passing, that the form is almost isolated, without the right to live as other people . This fight will make the people who have the virus circulating in the blood, people are not seen as abnormal, so they will subjectfied bearer of their condition, and relegate aids as a hitch that will have to overcome in their journey of life .